Subconscious Face Perception and Permanent Makeup - Luniaka, Antonina (Global Prosperity, 2025)
The article explores how permanent makeup influences the subconscious perception of the face, both by others and by the individual. The aim of the study is to identify how appearance changes caused by permanent makeup affect automatic cognitive-emotional evaluations of the face in social communication and self-perception. The study employed general scientific methods of cognition, including analysis, synthesis, modeling, systematization, comparison and generalization. The findings show that subconscious face perception occurs within fractions of a second before conscious thinking is activated. During these brief moments, the brain automatically integrates a range of visual cues, such as symmetry, proportionality of features, eye placement, the shape of eyebrows and lips, overall skin tone, and micro-expressions of emotion. Based on these parameters, an initial impression is formed, which includes perceived attractiveness, trustworthiness, emotional state, and the potential for safety or threat. This impression is a result of evolutionary adaptation aimed at enabling quick orientation in a social environment. It has been concluded that permanent makeup, by altering key aspects of appearance, can significantly influence these automatic reactions. Faces with permanent makeup are perceived by others as more defined, symmetrical, and emotionally readable, which subconsciously triggers positive social responses such as trust, openness, attractiveness, and emotional safety. At the same time, individuals with permanent makeup subconsciously interpret their reflection as more closely aligned with their internal self-image. This reduces anxiety, boosts self-esteem, and helps build a stable and positive identity. In this way, permanent makeup serves a dual purpose: it not only modifies the social impression projected by the face but also transforms the individual’s deep emotional self-perception. The practical significance of this study lies in the potential application of its findings in the fields of appearance psychology, image-making, and applied aesthetics.